Field-induced dynamics of a wave packet in a wide superlattice miniband - Meier, Torsten; von Plessen, G.; Feldmann, J.; Göbel, E.O.; Thomas, P.; Goossen, K.W.; Kuo, J.M.; Kopf, R.F. (International Quantum Electronics Conference)
In the absence of scattering mechanisms, a crystal electron subjected to a homogeneous electric field undergoes a periodic motion in both momentum and real space. This oscillatory motion is known as Bloch oscillations (BOs) and has recently been detected in transient four-wave mixing (FWM) and Tera-Hertz emission experiments on semiconductor superlattices. It is generally assumed that the minimum field required for the observation of BOs is controlled by the rate of scattering in the material. However, an experimental verification of this point is still lacking.

Direct verification of the existence of biexcitons in GaAs qauntum wells - Meier, Torsten; Smith, G.O.; Mayer, E.J.; Kuhl, J.; Schulze, A.; Bennhardt, D.; Koch, S.W.; Thomas, P.; Hey, R.; Ploog, K. (European Quantum Electronics Conference)
The strong nonlinear optical response of the 2D exciton in GaAs quantum wells at relatively low excitation densities has been observed in many experimental studies in accordance with theoretical predictions. In principle, exciton/exciton interaction results in a renormalization of the transition matrix elements, dephasing rates and frequencies of the excitonic states. Wang et al.1 claimed that all experimental results can be explained by a density- induced enhanced dephasing rate. In a previous paper,2 we have suggested a density dependent coupling between opposite spin excitons, which involves all three renormalization phenomena.

Interplay Between Inhomogeneous Broadening and Coulomb Interaction in the Dynamics of Excitonic Wave Packets - Meier, Torsten; Koch, M.; Jahnke, F.; Feldmann, J.; Schäfer, W.; Thomas, P.; Koch, S.W.; Göbel, E.O.; Nickel, H.
A proper description of subpicosecond four-wave-mixing (FWM) experiments for excitonic transitions in semiconductor heterostructures must consider the fact that the spectrally broad laser pulses excite not only the 1s bound exciton state but also energetically higher bound exciton states and the lower-lying part of the unbound continuum states. In this paper, we report results of transient and time-resolved FWM-experiments in which such ’excitonic wave packets’ play a crucial role. In addition, a theoretical treatment of the problem based on the solution of the semiconductor Bloch is presented. We show that the time-dependent nonlinear response is determined by an interplay between inhomogeneous broadening and Coulomb interaction.

Hinweise zur Statistik. Arbeitspapier - Tulodziecki, G.; Herzig, Bardo

Kreativität und Reproduktion. Annäherung an den Bildungshorizont von Ursula Weida - Schuster, Britt-Marie (Bausteine zu einer Geschichte des weiblichen Sprachgebrauchs. Forschungsberichte – Projektangebote – Forschungskontexte)
Keywords: Sprachliche Formelhaftigkeit/-Musterhaftigkeit

Leibniz als Identifikationsfigur der britischen Logiker des 19. Jahrhunderts - Peckhaus, Volker (VI. Internationalen Leibniz-Kongreß. Vorträge I. Teil, Hannover, 18.–22.7.1994)

Benno Kerry. Beiträge zu seiner Biographie - Peckhaus, Volker (History and Philosophy of Logic)
Abstracts: MR 94m:01033; Zbl. Math. 798.01016 (N.I. Osetinski); Philosopher’s Index 28.3 (Herbst 1994), 179.

Poisson Lie Groups and Non-LInear Convexity Theorems - Hilgert, Joachim; Neeb, K.-H. (Generalized Symmetries in Physics)

Radon Transform on Halfplanes via Group Theory - Hilgert, Joachim (Non-Compact Lie Groups and some of their Applcations)

A General Setting for Wiener-Hopf Operators - Hilgert, Joachim; Neeb, K.-H. (75 Years of Radon Transform)

The Geometry of Nilpotent Coadjoint Orbits of Convex Type in Hermitian Lie Algebras - Hilgert, Joachim; Neeb, K.-H.; Orsted, B. (J. Lie Theory)

Spherical Functions on Ordered Symmetric Spaces - Hilgert, Joachim; Faraut, J.; Ólafsson, G. (Ann. Inst. Fourier)

Symplectic Convexity Theorems and Coadjoint Orbits - Hilgert, Joachim; Neeb, K.-H.; Plank, W. (Compositio Math.)

A Convexity Theorems for Boundaries of Ordered Symmetric Spaces - Hilgert, Joachim (Canad. J. Math.)

Leptin, H. und J. Ludwig. Unitary Representation Theory of Exponential Lie Groups (De Gruyter, Berlin, 1994) - Hilgert, Joachim (Zentralblatt für Math.)

Die Osterfelder Pancratiuskirche und die Bottroper Cyriacuskirche als Indikatoren der frühmittelalterlichen Missionierung Westfalens - Englisch, Brigitte (Ursprünge und Entwicklungen der Stadt Oberhausen. Quellen und Forschungen zu ihrer Geschichte)

Die Artes liberales im frühen Mittelalter (5.-9. Jh.). Das Quadrivium und der Komputus als Indikatoren für Kontinuität und Erneuerung der exakten Wissenschaften zwischen Antike und Mittelalter - Englisch, Brigitte